Commentary and Notes on the Original Derivations of the Scharifker-Hills Model. Issue 3 (1st March 2023) - Sun, Yunkai; Zangari, Giovanni
Abstract : The Scharifker-Hills (S-H) model for the potentiostatic transients is one of the most widely utilized model in electrodeposition. With the concept of diffusion zones and the Kolmogorov-Johnson-Mehl-Avrami (KJMA) model, the occurrence of a peak current in the potentiostatic transient was elucidated. Unfortunately, the derivations of the S-H model had been scattered among several original papers. Herein, we have summarized the S-H model into the framework of the diffusion zone problem and compared the S-H model with the Classical model, the Scharifker and Mostany (S-M) model, the approach by Sluyters-Rehbach et al. (the SRWBS model), and the Heerman-Tarallo/Mirkin-Nilov (H-T/M-N) model.